Математическое моделирование электро¬магнитных полей в регулярных волноводах фрактальной природы методом R-функций - Максименко-Шейко, К.В.; Шейко, Т.И. (Проблемы машиностроения, 2010)
При описании объектов фрактальной геометрии используются следующие конструктивные средства теории R-функций: R-операции системы R0; суперпозиции функции ω(x, y) с периодическими функциями, позволяющие транслировать заданную функцию ω(x, y) вдоль осей и вдоль окружности; свойство подобия фигур; рекурсивные процедуры. Рассмотрены задачи нахождения Е- и Н-волн в регулярном волноводе с поперечным сечением в виде предфракталов – снежинок Коха, построенных на правильном треугольнике и квадрате. Достоверность полученных решений исследовалась с использованием метода мажорирующих областей. При описанні об'єктів фрактальної геометрії використовуються такі конструктивні засоби теорії R-функцій: R-операції системи R0; суперпозиції функції ω(x, y) з періодичними функціями, що дозволяють транслювати задану функцію ω(x, y) уздовж осей і уздовж окружності; властивість подоби фігур; рекурсивні процедури. Розглянуто задачі знаходження Е- та Н-хвиль у регулярному хвилеводі з поперечним перерізом у вигляді предфракталів – сніжинок Коха, побудованих на правильному трикутнику і квадраті. Вірогідність отриманих розв’язків досліджувалася з використанням методу мажоруючих областей. The fractal geometry objects (like as Serpinsky carpet, Koсh snowflake) began to be applied in a radio engineering at designing antenna devices and waveguides. The mathematical apparatus of the R-functions theory appeared rather convenient for the fractal geometry objects description. Thus the following constructive means are used: R-operations of system R0; superpositions of function ω(x, y) with the periodic functions, allowing to translate the given function ω(x, y) along axes and along a circle; property of similarity of figures; recursive procedures. Problems of finding Е-and Н-waves in a regular waveguide with cross section as Koсh snowflakes constructed on a regular triangle and a square are considered. Reliability of the received solutions was investigated with the help of majorizing areas method.